PENGARUH MODEL PEMBELAJARAN PROBLEM-BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA - Nasution, Ibrahim Yusup; Napitupulu, E. Elvis (Universitas Islam Sumatera Utara, 2024)
The research aims to determine the mathematical problem-solving abilities of students who are taught using the Problem-Based Learning model or direct learning model. As well as to see an overview of the process of students' mathematical problem-solving abilities in terms of the students' answer process. The population in this study was all students at SMP Negeri 2 Pantai Labu for the 2022/2023 academic year, totaling 210 students and the sample for this research was 61 students from class VIII-1 and class VIII-3. This type of research is experimental research. The data used is a PAM test with 15 questions and a mathematical problem-solving ability test in the form of a description with 3 questions. After the prerequisite tests are carried out, the data is declared Normal and Homogeneous, then the data can be carried out further tests. The results of data analysis of mathematical problem-solving abilities in the Problem-Based Learning learning model were an average of 63.439 with a standard deviation of 8.0608 and in the direct learning model the average was 45.727 with a standard deviation of 6.1296. To test the hypothesis, it was concluded that the mathematical problem-solving abilities of students taught using the Problem-Based Learning learning model were better than students taught using the direct learning model.